Functional constipation in Bangladeshi children: experience of demography and probable risk factors from a tertiary care hospital - Mazumder, Md. Wahiduzzaman; Sayeed, Maimuna; Benzamin, Md.; Chowdhury, Mahfuza (International Journal of Contemporary Pediatrics, 2020)
Background: Constipation is a common problem throughout childhood. It is important to be fully aware of the factors involved in developing constipation in children. There are few published articles on childhood constipation in Bangladesh. In this study, our aim was to evaluate demography and probable/potential risk factors for functional constipation in Bangladeshi children. Methods: The study was carried out among 179 children from May 2018 to June 2019 in the department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU) both indoor and outdoor basis. Children with constipation who fulfilled the ROME III criteria were evaluated for demography and probable/potential risk factors of constipation. Results: A total of 179 subjects were included in the final analysis. Among them, 54.75% were boys and 45.25% were girls. Constipation was found more in the age group above 5 years (56.42%), then in 2 to 5 years age group (33.52%) and lower in below 2 years of age (10.6%). Constipation was more among children living in urban area (55.3%) than in rural area (44.69%). Constipation was the presenting complaint in 76.54% subjects, other complaints were abdominal pain (47.49%), anorexia (24.02%), vomiting (19.56%). Diet low in fiber (72.63%) was found as the most common potential risk factor, other factors were ingestion of cow’s milk (32.96%), not having regular meals with parents (19.55%), consumption of junk foods (28.49%). Staying with grandparents (16.76%), living in hostel or madrasa / residential religious institute (5.03%), long period of academic activity, [homework (10.61%) / tutor and coaching (7.26%)], unhygienic toilet in school (6.14%) were also found to be probable associated factors in this study. Conclusions: Functional constipation was found more in boy’s and above five year age group. Low dietary fiber, consumption of cow’s milk and junk food, unwillingness to use toilets in school, long time in academic activity, were found to be potential underlying risk factors of constipation.